2020
DOI: 10.1001/jamainternmed.2020.5084
|View full text |Cite
|
Sign up to set email alerts
|

The Exclusion of Older Persons From Vaccine and Treatment Trials for Coronavirus Disease 2019—Missing the Target

Abstract: Older adults are at greatest risk of severe disease and death due to coronavirus disease 2019 (COVID-19). Globally, persons older than 65 years comprise 9% of the population, 1 yet account for 30% to 40% of cases and more than 80% of deaths. 2 Unfortunately, there is a long history of exclusion of older adults from clinical trials. In response, the National Institutes of Health instituted the Inclusion Across the Lifespan policy, requiring the inclusion of older adults in clinical trials. 3 Thus, we reviewed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 4 publications
(8 reference statements)
2
77
0
1
Order By: Relevance
“…Residents of long-term care facilities (LTCFs), particularly those in skilled nursing facilities (SNFs), have experienced disproportionately high levels of COVID-19–associated morbidity and mortality and were prioritized for early COVID-19 vaccination ( 1 , 2 ). However, this group was not included in COVID-19 vaccine clinical trials, and limited postauthorization vaccine effectiveness (VE) data are available for this critical population ( 3 ). It is not known how well COVID-19 vaccines protect SNF residents, who typically are more medically frail, are older, and have more underlying medical conditions than the general population ( 1 ).…”
mentioning
confidence: 99%
“…Residents of long-term care facilities (LTCFs), particularly those in skilled nursing facilities (SNFs), have experienced disproportionately high levels of COVID-19–associated morbidity and mortality and were prioritized for early COVID-19 vaccination ( 1 , 2 ). However, this group was not included in COVID-19 vaccine clinical trials, and limited postauthorization vaccine effectiveness (VE) data are available for this critical population ( 3 ). It is not known how well COVID-19 vaccines protect SNF residents, who typically are more medically frail, are older, and have more underlying medical conditions than the general population ( 1 ).…”
mentioning
confidence: 99%
“…They send a good signal for elderly, including those living in long terms care facilities or other institutions where corticosteroids could be prescribed according to an oxygen criterion, without systematic transfer to the hospital. Strengthening the therapeutic arsenal for the care of elderly with COVID-19 is critical as these patients may not fully benefit from vaccination because of the immune-senescence associated with advanced age and their exclusion from vaccine trials 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, among these patients, the RECOVERY trial found no difference in the survival of patients treated or not with dexamethasone 3 . However, the heterogeneity in the severity of infection within the latter subgroup limits the drawing of strong conclusions 4 . This situation has raised concerns and, in some countries, such as France, recommendations do not support the systematic use corticosteroids for patients ≥ 70 years old 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, the US National Institutes of Health instituted a new policy, Inclusion across the Lifespan 12 , requiring older adults to be enrolled into clinical trials. Despite these safeguards, in a recent study of 847 COVID-19 vaccine and treatment trials in clinicaltrials.gov 13 , 195 (23%) had an age cut-off and an additional 252 (30%) trials had other exclusions preferentially affecting older adults; thus, 447 (53%) of trials were considered high risk for excluding older adults. Of 18 vaccine trials, 11 (61%) had age-based exclusions, while 7 (39%) had other potential age-related exclusions; thus, 100% were considered high risk for excluding older adults.…”
Section: Commentmentioning
confidence: 99%